The innovation equation: balancing clever technical solutions with users' needs - Pawelka, G. E. F. (Procedia Engineering, 2010)
Finding clever technical solutions to clearly defined problems is just one half of the process of innovation. Innovation also includes identifying customers' sometimes well-concealed needs. If we can think of those factors associated with technology and those associated with user needs as being different terms on either side of a mathematical equation, innovation is the process of balancing the equation in a way that allows a clever solution to equal customers' needs. This paper explores the details of how important work on both sides of the equation resulted in the creation of a new sports training market that, prior to 1986, had not yet been fully contemplated.